Pharmacological Modification of Gastric Emptying: Effects of Propantheline and Metoclopromide on Paracetamol Absorption. Issue 5853 (10th March 1973) - Nimmo, J.; Heading, R. C.; Tothill, P.; Prescott, L. F.
Abstract : The rate of paracetamol absorption depends on the rate of gastric emptying. Propantheline delayed gastric emptying and markedly slowed the absorption of paracetamol in six convalescent hospital patients. Conversely, the absorption of paracetamol in five healthy volunteers was accelerated by metoclopramide, a drug which stimulates gastric emptying. The total 24-hour urinary excretion of paracetamol was not influenced by propantheline or metoclopramide. Other similar absorption interactions probably occur since drugs are poorly absorbed from the stomach and many therapeutic agents influence gastrointestinal motility.